ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) MENGGUNAKAN METODE JOB SAFETY ANALYSIS (JSA) DAN HAZARD IDENTIFICATION, RISK ASSESSMENT, AND RISK CONTROL (HIRARC) PADA BAGIAN PRODUKSI DI PT. XYZ - Fahrizal Gema Akbar; Hady Sofyan; Yayan Heru Haerudin (STKIP Pesisir Selatan, 2026)
Objective: Occupational Health and Safety (OHS) plays a strategic role in minimizing workplace accidents and improving productivity in manufacturing industries. Production processes involving press machines, welding robots, pre-tension machines, and assembly operations expose workers to various mechanical, physical, chemical, ergonomic, and electrical hazards. This study aims to identify occupational hazards, assess risk levels, and formulate appropriate risk control recommendations in the production department of PT. XYZ using the Job Safety Analysis (JSA) and Hazard Identification, Risk Assessment, and Risk Control (HIRARC) methods. Methods: This research employed a descriptive quantitative approach.. Results: The study identified 60 production activities containing 31 mechanical hazards (51.67%), 15 physical hazards (25.00%), 8 ergonomic hazards (13.33%), 4 electrical hazards (6.67%), and 2 chemical hazards (3.33%). Risk assessment showed that 7 activities (11.67%) were categorized as high risk, 28 activities (46.67%) as medium risk, and 25 activities (41.67%) as low risk. High-risk activities were mainly associated with press machine operation, welding robot movement, welding fumes, maintenance activities without Lock Out Tag Out (LOTO), and pre-tension machine operation.